Geochemical dataset of environmental samples from Idrija urban area, Slovenia - Bavec, Špela; Gosar, Mateja (Geologija, 2025)
This paper presents a dataset containing the results of geochemical analyses of three different urban materials- soil, sediment and household dust from the urban area of Idrija town (Slovenia). Topsoil, subsoil and garden soil were collected on the urban green surfaces. Sediments were collected in the gully pots of the urban drainage system (road sediments) and local streams flowing through Idrija’s urban area (stream sediments). Household dust was collected from the vacuum cleaner bags, which were provided by the residents. The geochemical analyses carried out were: (1) multi-elemental analysis (determination of element contents after modified aqua regia digestion by inductively coupled plasma (ICP) mass spectrometry and ICP emission spectrometry (ES) and (2) solid phase Hg thermo-desorption technique (determination of the relative amount of Hg binding forms). These two methods were applied to all investigated materials. Water leaching tests were carried out to determine the water-soluble Hg content in the urban soil by ICP-MS. A modified simulated stomach acid extraction in vitro tests were carried out to determine the bioaccessible Hg content in topsoil and household dust by ICP-MS. The dataset has a fundamental scientific value and is useful for local soil, sediment and household dust quality research, mitigation of pollution evaluation over time and assessment of environmental exposure and related health impacts.